PENERAPAN TEKNOLOGI CLIMATE SMART AGRICULTURE GUNA PENINGKATAN KAPASITAS DALAM MENDUKUNG RENCANA AKSI MITIGASI IKLIM DI BIDANG PERTANIAN - Pembengo, Wawan; Rahim, Yunnita (Jurnal Abdi Insani, 2025)
The agricultural sector is the third-largest contributor to greenhouse gas (GHG) emissions among the five major emitting sectors. In 2022, Indonesia strengthened its national commitment through the Enhanced NDC 2022, targeting a 31.89% reduction in emissions under the unconditional scenario and 43.20% under the conditional scenario with international support. Without significant climate-mitigation actions in agriculture, the goals of the Paris Agreement cannot be achieved. This community service program (Thematic Community Service Program – Phase 2) was conducted in Boidu Village, North Bulango District, Bone Bolango Regency, Gorontalo Province, for 45 days using training and mentoring approaches to support the application of scientific and technological innovations. The activities also served as action research to promote Climate Smart Agriculture (CSA) technologies, including agroforestry systems, water-harvesting techniques (biopores and rorak pits), and the decarbonization of rice straw and husks. This program successfully demonstrated the practical implementation of CSA as a strategy for climate-change mitigation and adaptation in the agricultural sector. Three key technologies—agroforestry, water harvesting (biopores and rorak), and straw/husk decarbonization—were shown to produce synergistic benefits. Agroforestry enhances ecosystem complexity and carbon stocks, water-harvesting techniques optimize hydrological cycles and reduce erosion, and the decarbonization of straw and husks converts agricultural waste into biochar, functioning as long-term carbon storage while improving soil fertility.